1995
DOI: 10.1111/j.1365-2672.1995.tb05030.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural wine yeasts as biocontrol agents

Abstract: A total of 586 natural wine yeasts, belonging to different genera, were tested for their antagonistic effect on fungal pathogens. A low percentage of yeast strains completely inhibited the pathogens and the biocontrol activity was found to be a strain characteristic and did not solely depend on species or genus. Among the antagonists, two strains of Saccharomyces cerevisiae and one of Zygosaccharomyces showed a broad spectrum of antagonistic activity against 10 fungal pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 15 publications
2
28
0
4
Order By: Relevance
“…The yeasts in such studies included the genera Debaryomyces (Santos et al 2004), Kloeckera (McLaughlin et al 1992, Sporothrix (Hajlaoui and Bèlanger 1993), Saccharomyces, Zygosaccharomyces (Suzzi et al 1995), Sporobolomyces (Janisiewicz et al 1994;Filonow 1998), Metschnikowia (Karabulut et al 2004), Tilletiopsis (Ng et al 1997), Rhodotorula Sansone et al 2005), Cryptococcus (Anderson et al 1997;Lima et al 1998), Aureobasidium (Castoria et al 2001;Ippolito et al 2005), Pichia (Masih and Paul 2002;Santos et al 2004), andCandida (McLaughlin et al 1992;Gamagae et al 2004).…”
Section: Mechanisms Of Antagonismmentioning
confidence: 99%
See 2 more Smart Citations
“…The yeasts in such studies included the genera Debaryomyces (Santos et al 2004), Kloeckera (McLaughlin et al 1992, Sporothrix (Hajlaoui and Bèlanger 1993), Saccharomyces, Zygosaccharomyces (Suzzi et al 1995), Sporobolomyces (Janisiewicz et al 1994;Filonow 1998), Metschnikowia (Karabulut et al 2004), Tilletiopsis (Ng et al 1997), Rhodotorula Sansone et al 2005), Cryptococcus (Anderson et al 1997;Lima et al 1998), Aureobasidium (Castoria et al 2001;Ippolito et al 2005), Pichia (Masih and Paul 2002;Santos et al 2004), andCandida (McLaughlin et al 1992;Gamagae et al 2004).…”
Section: Mechanisms Of Antagonismmentioning
confidence: 99%
“…Many of the antibiosis studies involve either pairing of colonies on agar plates using different solid substrates and measuring inhibition zones (Suzzi et al 1995;Walker et al 1995;Spadaro et al 2002), screening of the culture filtrates for inhibition of vegetative growth and spore germination of fungal pathogens in vitro, or utilizing artificially wounded fruits (Spadaro et al 2002) or leaves (Masih et al 2001) coinoculated with the antagonists and the pathogens. Suzzi et al (1995) reported that natural wine yeasts belonging to Saccharomyces and Zygosaccharomyces inhibited in vitro growth of soil-borne fungal plant pathogens including Rhizoctonia fragariae, Sclerotinia sclerotiorum, and Macrophomina phaseolina.…”
Section: Antibiosismentioning
confidence: 99%
See 1 more Smart Citation
“…В себестоимости продуктов животноводства 65-70 % затрат приходится на корма, поэтому полноценное питание животных и правильная организация кормления занима-ют ведущую роль в интенсификации производства [14].…”
Section: применение дрожжей и продуктов их переработки для кормления unclassified
“…Some yeast species, in particular Pichia guilliermondii and P. anomala, inhibit the growth of certain moulds attacking fruits during postharvest storage (Wisniewski and Wilson 1992;Suzzi et al 1995). Conversely, a large number of mycelial fungi can attack yeasts.…”
Section: Yeasts and Moldsmentioning
confidence: 99%